THE TRANSATLANTIC TRADE DISPUTE CONCERNING GENETICALLY MODIFIED ORGANISMS – WTO-CONSISTENCY OF THE EC LABELLING SCHEME - Hoehn, Christiane (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2002)
This article examines the WTO-consistency of the EU labelling scheme on Genetically Modified Organisms (GMO). This regulation, requiring the labelling of authorised GMO food and feed placed on the market in the EU, presents serious economical as well as practical implications for US producers. At the heart of the debate are the different risk perceptions as well as regulatory approaches on both sides of the Atlantic. After a brief presentation of the European labelling scheme, the author examines its compliance with several agreements within the WTO international trading regime, namely the Sanitary and Phytosanitary Standards Agreement (SPS), the Technical Barriers in Trade Agreements (TBT) as well as basic GATT rules. Her analysis brings her to the conclusion that despite the non-application of the SPS agreement, the EU labelling scheme is in conformity of both the TBT and the basic GATT rules. The overall aim of the article is not only to present a legal analysis of one of the issues on the front burner of the global trade talks, but also to underline the difficulty in drawing the line between international free trade and domestic regulation expressing other values and objectives that affect trade as a non-tariff barrier.